The disease of dental caries, taking into account the timing of eruption and mineralization of permanent teeth in children in the City of Bukhara - M. Sh. Afakova (Research Parks Publishers, 2021)
There is a work by F. L. Mirsalikhova devoted to the study of the degree of mineralization with the timing of the eruption of the first permanent molars in children of the city of Tashkent. Based on the above, the study of the timing of eruption and mineralization of permanent teeth in children is very relevant, has great practical and theoretical significance, since the results obtained will be taken into account when organizing dental care for children in our Republic.